2020
DOI: 10.1177/2050312120962995
|View full text |Cite
|
Sign up to set email alerts
|

English language proficiency, complete tooth loss, and recent dental visits among older adults in the United States

Abstract: Objectives: This study sought to provide population-based estimates of complete tooth loss and recent dental visits among older adults in the United States by English language proficiency. Methods: We conducted a cross-sectional analysis of the 2017 Medical Expenditure Panel Survey among participants ⩾50 years of age (n = 10,452, weighted to represent 111,895,290 persons). Five categories of language proficiency were created based on self-reported English language ability and language spoken at home (Spanish, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, this study found an increasing percentage of patients with limited language proficiency over time (0.26% to 1.44%), which also included an increasing diversity of languages spoken (n = 4 to n = 21) over the same time period. These data are significant as recent studies have shown that limited language proficiency may be increasingly associated with gaps in healthcare coverage, lower levels of insurance and public assistance qualification, as well as decreased measures of oral health [54][55][56]. In fact, many studies have confirmed that non-English, non-Spanish speaking patients and households experience additional barriers and needs beyond those typically associated with low-income and low-SES populations, which may suggest additional resources are needed to reach them in language-and culturally appropriate ways [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…For example, this study found an increasing percentage of patients with limited language proficiency over time (0.26% to 1.44%), which also included an increasing diversity of languages spoken (n = 4 to n = 21) over the same time period. These data are significant as recent studies have shown that limited language proficiency may be increasingly associated with gaps in healthcare coverage, lower levels of insurance and public assistance qualification, as well as decreased measures of oral health [54][55][56]. In fact, many studies have confirmed that non-English, non-Spanish speaking patients and households experience additional barriers and needs beyond those typically associated with low-income and low-SES populations, which may suggest additional resources are needed to reach them in language-and culturally appropriate ways [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The study of effective communication in delivering cross‐cultural patient care is an important issue in dental education. Language barriers present a significant obstacle to accessing dental care services, 1 as those with limited English proficiency discontinue care during active treatment more often with lower rates of routine recall 2 and are less likely to establish a dental home 3 . Specifically, Spanish‐speaking Hispanics experience poor oral health outcomes and obtain irregular dental care 4 .…”
Section: Introductionmentioning
confidence: 99%